Analisis Pemilihan Supplier Frozen Food untuk Meningkatkan Kinerja UMKM Menggunakan Metode AHP - Yusron Fanani (Industrial & System Engineering Journals (ISEJOU), 2023)
Competition in the developing world of the MSME industry makes MSME businesses required to be able to compete to be in the best position among other MSME businesses that are increasingly popping up and maintaining their existence. Naisha Frozen Food is a business engaged in the field of refrigerated food using a freezer in order to preserve food so it doesn't go through a process of decomposition that is too fast. This study aims to select suppliers for Naisha Frozen Food. In addition, this study uses the Analytical Hierarchy Process (AHP) method to analyze each data. In increasing profits, Naisha Frozen Food selects suppliers according to the criteria so that demand increases. Based on the research that has been done, the criteria for Naisha Frozen Food are price, quality, taste, service, and delivery. The priority for selecting the supplier with the highest value, namely the price and results of the supplier having the highest value, is supplier 1 (Pekarungan Village).